2023
DOI: 10.1038/s41598-023-37435-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of WeChat guidance on bowel preparation for colonoscopy: a quasi-experiment study

Abstract: Colonoscopy is a standard procedure for screening, monitoring, and treating colorectal lesions. To explore the impact of WeChat guidance on bowel preparation before colonoscopy. This quasi-experiment study included patients who underwent colonoscopy at Qingdao Endoscopy Center between March 2016 and September 2016. The primary outcome was bowel preparation quality (Ottawa score), the secondary outcomes were intubation time, withdrawal time, adenoma detection rate (ADR), and adverse reactions. Finally, 588 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…zander Team independently developed a smartphone application, patients can run the application on android or ios equipment, the application provides information and conventional hospital education content is very similar, but the way of information is more intuitive, namely according to the patient appointment colonoscopy time customization, provide patients need to achieve intestinal cleaning degree of low residue food image, laxative intake method and image, provide personalized intestinal preparation steps, the results showed that the quality of gut preparation was significantly better in the smartphone app population compared to the control group [5]. Guan Y Team uses WeChat, a smart Chinese instant messaging and social media application, let colonoscopy or their families in booking time scan or codes WeChat group, the medical staff WeChat group with text, pictures, videos telling the importance of intestinal preparation, dietary requirements, and diarrhea drug medication instructions, etc., the results show that using WeChat group, can improve the quality of intestinal preparation and increase the adenoma detection rate, shorten the total time of colonoscopy, and reduce the discomfort in intestinal preparation [6]. In clinical work, the workload of clinical medical staff is heavy, and the simple propaganda and education efficiency is low.…”
Section: Preoperative Education and Bowel Preparationmentioning
confidence: 97%
“…zander Team independently developed a smartphone application, patients can run the application on android or ios equipment, the application provides information and conventional hospital education content is very similar, but the way of information is more intuitive, namely according to the patient appointment colonoscopy time customization, provide patients need to achieve intestinal cleaning degree of low residue food image, laxative intake method and image, provide personalized intestinal preparation steps, the results showed that the quality of gut preparation was significantly better in the smartphone app population compared to the control group [5]. Guan Y Team uses WeChat, a smart Chinese instant messaging and social media application, let colonoscopy or their families in booking time scan or codes WeChat group, the medical staff WeChat group with text, pictures, videos telling the importance of intestinal preparation, dietary requirements, and diarrhea drug medication instructions, etc., the results show that using WeChat group, can improve the quality of intestinal preparation and increase the adenoma detection rate, shorten the total time of colonoscopy, and reduce the discomfort in intestinal preparation [6]. In clinical work, the workload of clinical medical staff is heavy, and the simple propaganda and education efficiency is low.…”
Section: Preoperative Education and Bowel Preparationmentioning
confidence: 97%